Selective Modulation of MicroRNA Expression with Protein Ingestion Following Concurrent Resistance and Endurance Exercise in Human Skeletal Muscle - Camera, Donny M.; Ong, Jun N.; Coffey, Vernon G.; Hawley, John A. (Frontiers in Physiology, 2016)
We examined changes in the expression of 13 selected skeletal muscle microRNAs (miRNAs) implicated in exercise adaptation responses following a single bout of concurrent exercise. In a randomized cross-over design, seven healthy males undertook a single trial consisting of resistance exercise (8 × 5 leg extension, 80% 1 Repetition Maximum) followed by cycling (30 min at 70% VO2peak) with either post-exercise protein (PRO: 25 g whey protein) or placebo (PLA) ingestion. Muscle biopsies (vastus lateralis) were obtained at rest and 4 h post-exercise. Detection of miRNA via quantitative Polymerase Chain Reaction (qPCR) revealed post-exercise increases in miR-23a-3p ( 90%), miR-23b-3p ( 39%), miR-133b ( 80%), miR-181-5p ( 50%) and miR-378-5p ( 41%) at 4 h post-exercise with PRO that also resulted in higher abundance compared to PLA (P<0.05). There was a post-exercise decrease in miR-494-3p abundance in PLA only ( 88%, P<0.05). There were no changes in the total abundance of target proteins post-exercise or between conditions. Concurrent exercise can modulate the expression of miRNAs implicated in exercise adaptations. The selective modulation of miRNAs with target proteins that may prioritise myogenic compared to oxidative/metabolic adaptive responses indicate that miRNAs can play a regulatory role in the molecular machinery enhancing muscle protein synthesis responses with protein ingestion following concurrent exercise.